2015
DOI: 10.1080/07373937.2015.1069327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feed Composition and Drying Parameters on the Surface Composition of a Spray-Dried Multicomponent Particle

Abstract: Surface properties of multicomponent particles produced in spray drying can be controlled by selective accumulation of specific components, which are present in the liquid feed, on the particle surface. Such modification of the surface composition can take place only before a solid shell forms on the particle surface. In this contribution the influence of the concentration of surface active component on modifications of the surface composition is discussed. Based on results of single droplet drying simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since measuring and approximation tools for Maxwell-Stefan multicomponent diffusion coefficients in concentrated aqueous solutions are lacking, the parameters of the diffusivity equations had to be fitted so that the simulated concentration profiles agreed with the experimental results. In the modeling work by Porowska et al (2015) on drying whey protein/sucrose droplets, the phenomena taking place during crust formation were largely disregarded. The focus was laid on the surface activity of the whey protein, and it was supposed that the adsorption process would halt upon commencing shell formation.…”
Section: Approaches With Spatiotemporal Multicomponent Mass Balancesmentioning
confidence: 99%
“…Since measuring and approximation tools for Maxwell-Stefan multicomponent diffusion coefficients in concentrated aqueous solutions are lacking, the parameters of the diffusivity equations had to be fitted so that the simulated concentration profiles agreed with the experimental results. In the modeling work by Porowska et al (2015) on drying whey protein/sucrose droplets, the phenomena taking place during crust formation were largely disregarded. The focus was laid on the surface activity of the whey protein, and it was supposed that the adsorption process would halt upon commencing shell formation.…”
Section: Approaches With Spatiotemporal Multicomponent Mass Balancesmentioning
confidence: 99%
“…Powder formation, for example by spray drying, may influence powder properties that influence rehydration (Gaiani et al, 2010). Porowska et al (2015) showed that spray drying parameters and feed composition can be manipulated to influence the surface composition which can influence wetting behaviour.…”
Section: Introductionmentioning
confidence: 99%